The function of the Quranic witness In the grammatical guidance of the Quranic readings An applied study of some of its evidence (Journal of the College of Basic Education, 2023)
Praise be to God, Lord of the worlds, and prayers and peace be upon our master Muhammad and his family and companions.Praise be to God, who blessed the Arabs with the revelation of the Noble Qur’an, which preserved its eloquence for Arabic, so its words were explained with clarity, challenging mankind and jinn in its miraculousness. It is based on expression, building and formulating rules.What is wrong with the grammarians is that they did not stop at the Qur’anic evidence for a moment of contemplation, as they did not arouse the minds of the addressee to the subtle linguistic sense, due to their arbitration by logic through the interpretation of the verses of the Qur’an that contradict their measurements – especially the visual ones – which sometimes missed them – accuracy in standing on the essence of Arabic usages and their moral realities. .This does not mean that the Basrans alone were extravagant in interpretation and appreciation by moving away from the linguistic sense. The Basrans and the Kufians approached that - as it will become clear to us - for the purpose of reconciling the eloquent texts with their grammatical rules.In this research, we discuss the importance of the Qur'anic witness and its function in enhancing the citation of the Qur'anic readings in building rules, directing linguistic uses, and understanding their implications.